Endogenous price leadership: A theoretical and experimental analysis - Werner Güth; Kerstin Pull; Manfred Stadler; Alexandra Zaby (University of Tübingen, Faculty of Economics and Social Sciences, 2014)
We present a model of price leadership on homogeneous product markets where the price leader is selected endogenously. The price leader sets and guarantees a sales price to which followers adjust according to their individual supply functions. The price leader clears the market by serving the residual demand. As price leaders, firms with different marginal costs induce different prices. We compare two mechanisms to determine the price leader, majority voting and competitive bidding. According to the experimental data at least experienced price leaders with lower marginal costs choose higher prices. In the bidding treatment, compensation payments to the price leader crowd in efficiency concerns.
urn:nbn:de:bsz:21-opus-72073
Keywords: D43; D74; L11; 330; price leadership; majority voting; bidding; experimental economics